A comparative look at the economic and environmental performances of India and China - Risto Herrala (Bank of Finland, Bank of Finland Institute for Emerging Economies (BOFIT), 2024)
We compare the economic and environmental performances of India and China over the past decade against the Euro Area, Japan, and the USA. India has emerged as the world's fastest growing large economy, but closer scrutiny suggests this impressive economic performance derives largely from structural factors such as labor force growth and the Balassa-Samuelson effect. Indeed, notwithstanding its superior level of economic development relative to India, China still posts stronger economic gains from investment and total factor productivity growth. While the two economies have grown markedly faster than the three developed economies against which we compare them, both Indian and Chinese growth has come with huge increases in greenhouse gas emissions. Our findings underscore the importance of Chinese and Indian participation in efforts to avoid the more dire impacts of climate change.
urn:nbn:fi-fe2024041016031
Keywords: 330; India; China; economic growth; CO2 emissions